Determination of the main stages of mixing wheat sourdough relative method - Dolomakin, Yuriy (My University, 2016)
The optimum duration of the cooking liquid wheat sourdough for the proposed design of the mixer was determined by fixing the beginning of time, during which the amount of torque on the outside of the mixing bowl was at the same level for a certain period of time. Slots began to form structures have been identified in the system of the flour/water, the time to reach the maximum resistance of the system, and the start time balancing system as an indirect factor in product availability.
Keywords: sourdough; mixing time; structure; torque; 3D printing; опара; час змішування; момент; 3D друк; время смешивания; структура; кафедра машин і апаратів харчових та фармацевтичних виробництв